Association between biotin deficiency and FOXP3 gene polymorphism (rs3761548) in patients with rheumatoid arthritis - Arjeen Abdullah; Najat Berwary (The Egyptian Journal of Internal Medicine, 2026)
Abstract Background Rheumatoid arthritis (RA) is a common inflammatory disease characterized by synovial tissue swelling and inflammation that results in joint destruction and dysfunction. This study was a first evaluation of serum biotin levels in patients with RA and the relationships with disease activity score (DAS28). The current study aimed to determine whether there is a deficiency in serum biotin concentration, to explore its relationship with disease severity, and to investigate whether the polymorphism in the forkhead box P3 ( FOXP3 ) gene (rs3761548) is a risk factor among patients with RA and if this polymorphism influences serum biotin concentration. Materials and methods This case-control study involved the examination of 136 RA patients and 85 as a control group. Serum biotin concentration was measured by Enzyme-Linked Immunosorbent Assay (ELISA), DNA sequencing was performed by Sanger sequencing, and the DAS28 was also evaluated for all patients. Results The serum biotin levels in the control group were significantly higher than those in the patient group ( p -value: